Attitudes towards breastfeeding among mothers of children treated at the University Children's Hospital in Lublin - Jankowska, Paula; Jankowski, Krzysztof; Tarkowska, Agata; Haracz, Jakub; Tadla, Monika (Journal of Education, Health and Sport, 2019)
IntroductionAccording to the current state of knowledge, breastfeeding is the best method of feeding newborns, infants and young children. World organizations and associations and authorities of the medical world recommend breast milk as the most suitable for the proper development of the child. Natural feeding brings many important health benefits, both for the mother and the child, and promotes the formation of emotional ties. It is also economical and convenient to use.The purpose of the studywas to assess the attitudes of women towards breastfeeding and the state of their knowledge on the subject.Material and methodsThe study group consisted of 96 mothers of children treated in the Department of Neonate and Infant Pathology at the University Children's Hospital in Lublin. The study used the method of a diagnostic survey using a questionnaire constructed by the authors. The obtained results were analyzed using the STATISTICA 12.5 program.Results53.9% of respondents gave a positive answer to the question about breastfeeding their own child. As the main reasons for its interruption were given most often too little food (36.6%) and child's illness (26.8%). 79.8% of women replied that the help of health care workers in breastfeeding training is needed, but only 56.2% of respondents believe that the information obtained was sufficient. Only 41.6% of respondents knew that lactation affects fertility and the possibility of becoming pregnant. In the question whether breastfeeding allows a better relationship between the mother and the child, 95.5% gave a positive answer. 98.9% emphasized the positive impact of breastfeeding on the relationship between parents. As many as 60.7% of women intended to give up natural feeding after returning to work.ConclusionsA surprisingly high percentage of women resign from natural feeding, despite relatively good knowledge about the benefits resulting from it. Advice from healthcare professionals is an important source of information for women. Breastfeeding after returning to work is an important problem.